EXTRACURRICULAR WORK AS AN EDUCATIONAL MEANS PROFESSIONAL EDUCATION (Pedagogy of Higher and Secondary Education, 2008)
The attempt to define components of system of extracurricular pedagogical work as an educational mean of professional education is made in this article.